Linking hydrologic regime, rainfall and leaf litter fall in a riverine forest within the ramsar site humedales Chaco (Argentina) - Casco, Sylvina Lorena (2016)
Fil: Casco, Sylvina Lorena. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.